Think-Pair-Share (Tps) Learning Model In Improving Student Pediatric Learning Outcomes Mts. Tarbiyatul Islam Sumberkerang Gending Probolinggo - Hadi, Samsul; Kusmawati, Wiwik; Khozanah Ilmah, Nur; Kurniawan, Rubbi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aim of this research is to improve the PJOK learning outcomes of MTs.Tarbiyatul Islam Sumberkerang Gending Probolinggo students with the Think Pair Share learning model. Data analysis techniques were used to examine all the data that had been collected while the researcher carried out the practice of implementing the TPS model in class X A through PJOK lessons at MTs.Tarbiyatul Islam Sumberkerang Gending Probolinggo. Data comes from observations, interviews, tests and other data. Data analysis was carried out in three stages, namely: data reduction, data display (data presentation), conclusion drawing/verification (drawing conclusions). Using the Think-Pair-Share learning model can improve PJOK learning outcomes for class X A students at MTs.Tarbiyatul Islam Sumberkerang Gending Probolinggo. This can be seen from the increase in learning completeness criteria when before action was taken, it was 0%, after action in cycle I it increased to 45,1% while after action in cycle II it increased again to 87,1%.